A Comparative Evaluation of Risk Factors and Various Antibiotic Regimens in Postoperative Neurosurgical Infections: A Prospective Randomized Controlled Study - Shetty, R.; Dwarakanath, S.; Veena Kumari, H.B.; Sampath, S.; Chandramouli, B.A. (Indian Journal of Neurosurgery, 2017)
Introduction Postoperative neurosurgical infections are a major problem, and the importance of keeping them to an absolute minimum cannot but be overemphasized. In this prospective study, we plan to evaluate the efficacy of three antibiotic regimens designed keeping the availability, affordability, and efficacy upon the common bacterial flora isolated at our center. We will also analyze the incidence and evaluate the risk factors of surgical site infections following clean, nonimplant, fresh, elective craniotomies.Material and Methods This prospective randomized control study was conducted at our institute, a tertiary referral center, for a period of 2 years. The study cohort included all patients undergoing clean, nonimplant, fresh, elective craniotomies at our institute. The antibiotic protocol was chosen according to the current bacterio-epidemiological data based on the prevalence of infectious agent. One of the three drug regimens was chosen.Results The results of univariate analysis revealed that there are multiple factors that are significantly associated with postoperative surgical site infection. In the multivariate analysis, only the presence of cerebrospinal fluid leak was the most significant factor associated with postoperative infections. Among the three different antibiotic regimens, cefazolin and amoxicillin–clavulanic acid were much better prophylactic agents for preventing surgical site infections when compared with cefotaxime.Conclusion The present study has provided an insight into the incidence and risk factors contributing to surgical site infections as well as the efficacious antibiotic regimen protocols. The present study is one of the few studies to compare the efficacy of different antibiotic regimen protocols and also prospectively analyze the factors contributing to postoperative infections. This study will help us in optimizing the prophylaxis protocols and prevent emergence of multidrug-resistant strains, especially in a country like India.
Keywords: antibiotics; infections; cefazolin; Amoxicillin–clavulanic acid; cefotaxime